2019
DOI: 10.21608/ajs.2019.43662
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION FOR MECA GENE IN EGYPTIAN CLINICAL Staphylococcus aureus SAMPLES AND STUDY THEIR GENOTOXIC ACTIVITY

Abstract: Staphylococcus aureus isolates were isolated from fifty clinical samples collected from Ain Shams University Hospitals (March-July 2016) and identified using biochemical and microbiological tests. PCR was performed using specific primers to determine the isolates of Methicillin-Resistant Staphylococcus aureus (MRSA) based on the presence of mecA gene. Thirty-four isolates from total fifty isolates (68%) were identified as MRSA isolates. To study the genotoxicity for this isolates, forty-five mice were injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…In our study, mecA gene was detected in 40 % of Staphylococcus aureus isolates; these results are near to the results reported by Hassan et al 21 who reported prevalence of MRSA in cultures from tropics (73%), sub-tropics (39%) and temperate (54%) regions , on Controversy to our results were less than those reported by Anand et al 22 who performed PCR for amplification of the mecA gene in Fifty strains of S. aureus and showed that 32 isolates were mecA gene positive with 64% MRSA prevalence rate, and also less than those reported by Marwa et al 23 in 2019 (MRSA prevalence was (68%).…”
Section: Discussioncontrasting
confidence: 71%
“…In our study, mecA gene was detected in 40 % of Staphylococcus aureus isolates; these results are near to the results reported by Hassan et al 21 who reported prevalence of MRSA in cultures from tropics (73%), sub-tropics (39%) and temperate (54%) regions , on Controversy to our results were less than those reported by Anand et al 22 who performed PCR for amplification of the mecA gene in Fifty strains of S. aureus and showed that 32 isolates were mecA gene positive with 64% MRSA prevalence rate, and also less than those reported by Marwa et al 23 in 2019 (MRSA prevalence was (68%).…”
Section: Discussioncontrasting
confidence: 71%